2015
DOI: 10.2500/ajra.2015.29.4165
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Binostril versus Transnasal Transseptal Microscopic Pituitary Surgery: Sinonasal Quality of Life and Olfactory Function

Abstract: Transnasal transseptal microscopic pituitary surgery confers a better early postoperative sinonasal QOL with a comparable olfactory outcome compared with the endoscopic approach. Although many believe that an endoscopic approach is less invasive, preservation of the sinonasal mucosa proves to be more important in terms of sinonasal QOL than use of an endoscope or microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…Endoscopic cases had a better rhinological outcome. Hong et al compared outcomes of patients undergoing unilateral microscopic and bilateral endoscopic surgery using the ASK nasal inventory, a derivative of the recently introduced ASK Nasal‐12; microsurgical cases showed better scores 3 months after surgery . Here, a further follow‐up would be necessary.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Endoscopic cases had a better rhinological outcome. Hong et al compared outcomes of patients undergoing unilateral microscopic and bilateral endoscopic surgery using the ASK nasal inventory, a derivative of the recently introduced ASK Nasal‐12; microsurgical cases showed better scores 3 months after surgery . Here, a further follow‐up would be necessary.…”
Section: Discussionmentioning
confidence: 79%
“…Hong et al compared outcomes of patients undergoing unilateral microscopic and bilateral endoscopic surgery using the ASK nasal inventory, a derivative of the recently introduced ASK Nasal-12; microsurgical cases showed better scores 3 months after surgery. [17][18][19] Here, a further follow-up would be necessary. In another comparative study of microscopical and bilateral endoscopical surgery, Pledger et al found no significant difference between the late postoperative SNOT-20 scores.…”
Section: Discussionmentioning
confidence: 99%
“…This approach offers improved illumination and superior panoramic visualization of the sella and the surrounding structures [35]. Compared with traditional sublabial or transseptal microscopic approach, ETSS offers minimal invasiveness, fewer complications, and overall improved outcomes [6, 7]. Traditionally, there are two approaches to endoscopic transsphenoidal surgery for pituitary adenomas: the two nostrils (binostril) approach and the one nostril (mononostril) approach [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, there are increased risks of rhinological complications and postoperative discomfort. Recent studies have shown that BETA presents poor early-postoperative sinonasal QOL and a significant olfactory alteration [6, 11, 12]. Many cases reported better results using the mononostril approach [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al 15 reports that CT-assisted surgery is associated with lower CSF leak rates compared to no image guidance or MRassisted procedures; the authors recognize the limitation of this report was the inability to control for the severity or extent of the disease. Hong et al 16 studied olfactory function and quality of life in patients undergoing endoscopic binostril or transnasal transseptal microscopic pituitary surgery. They report that transnasal transseptal surgery is associated with better postoperative quality of life and similar olfactory function when compared with the endoscopic approach.…”
mentioning
confidence: 99%